The Effect of Intergenerational Trauma on Marital Stability: The Mediating Roles of Cognitive Emotion Regulation, Trust, and Intimacy - Vakacegu, Jone; Brooks, Nathaniel (Applied Family Therapy Journal (AFTJ), 2026)
Objective: The present study aimed to examine the effect of intergenerational trauma on marital stability among married adults in Canada and to investigate the mediating roles of cognitive emotion regulation, trust, and intimacy in explaining this relationship.Methods and Materials: This study employed a cross-sectional correlational design using structural equation modeling (SEM). The study population consisted of married adults residing in Canada. A total of 642 participants were recruited through community organizations, counseling centers, social media platforms, and online advertisements, of whom 618 completed questionnaires were retained for analysis after data screening. Participants completed the Intergenerational Trauma Scale, Cognitive Emotion Regulation Questionnaire (CERQ), Dyadic Trust Scale, Personal Assessment of Intimacy in Relationships (PAIR), and Marital Stability Scale. Data were analyzed using SPSS 29 and AMOS 29. Descriptive statistics, Pearson correlation analyses, confirmatory factor analysis, and structural equation modeling were performed. The significance of indirect effects was assessed using bootstrapping procedures with 5,000 resamples and 95% confidence intervals.Findings: The structural model demonstrated excellent fit to the data (χ²/df = 2.37, CFI = 0.961, TLI = 0.955, RMSEA = 0.047, SRMR = 0.039). Intergenerational trauma negatively predicted cognitive emotion regulation (β = -0.48, p < .001), trust (β = -0.35, p < .001), intimacy (β = -0.28, p < .001), and marital stability (β = -0.21, p < .001). Cognitive emotion regulation positively predicted trust (β = 0.39, p < .001), intimacy (β = 0.26, p < .001), and marital stability (β = 0.18, p < .001). Trust significantly predicted intimacy (β = 0.51, p < .001) and marital stability (β = 0.29, p < .001). Intimacy emerged as the strongest direct predictor of marital stability (β = 0.46, p < .001). Bootstrapping analyses confirmed significant indirect effects of intergenerational trauma on marital stability through cognitive emotion regulation, trust, and intimacy (β = -0.42, p < .001), indicating partial mediation. The model explained 71% of the variance in marital stability.Conclusion: The findings demonstrate that intergenerational trauma exerts a substantial negative influence on marital stability through its detrimental effects on emotional regulation, interpersonal trust, and intimacy.